Laboratory investigation on hydraulic anisotropy behavior of unsaturated soil - Priono (2017)
Hydraulic anisotropy behavior of unsaturated soil has not been fully investigated. Direct laboratory measurement and indirect determination of hydraulic anisotropy under a drying condition were carried out on statically compacted specimens having different initial conditions. Direct measurement of permeability was carried out using an unsaturated triaxial permeameter whereas indirect determination of permeability was performed through statistical estimation via a measured drying soil–water characteristic curve (SWCC). In this research, two orientations — specifically horizontal-layering (HL) and vertical-layering (VL) orientations — were prepared for a given specimen from statically compacted homogeneous sand–kaolin. The results from both direct measurement and indirect determination of hydraulic anisotropy were in good agreement. Hydraulic anisotropy under an unsaturated condition was found to be similar with that in a saturated condition. Moreover, hydraulic anisotropy was reflected in the ratio of transient time during the direct measurements of HL and VL specimens at high matric suctions. In contrast, in the indirect method, hydraulic anisotropy was reflected in the ratio of equalization time during SWCC tests at matric suctions higher than the air-entry value of the soil.